1999
DOI: 10.1007/pl00012135
|View full text |Cite
|
Sign up to set email alerts
|

Distribution patterns of bacterioplankton and chlorophyll-a in the German Wadden Sea

Abstract: In a first synoptic evaluation, the temporal and spatial distribution of bacterioplankton and chlorophyll-a were determined in the German Wadden Sea. Three surveys were undertaken in winter, spring, and summer of 1994 using up to eight ships simultaneously between the river Ems and Sylt island. Despite intensive hydrodynamic mixing of the Wadden Sea water, spatial gradients were obvious. The abundance of bacterioplankton ranged from 0.4 to 26×10 5 ml -1 and chlorophyll-a varied between <0.1 and 79 µg l -1 . In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
3
1
1
Order By: Relevance
“…Our bacterial numbers are well in the range of other studies on the Wadden Sea (Admiraal et al 1985, Van Duyl & Kop 1988, Grossart et al 2004. Poremba et al (1999b) reported lower numbers from the North Frisian Wadden Sea. Please note that we only assessed total bacterial numbers in the water column and did not differentiate between the free-living and aggregate-associated fractions.…”
Section: Suspended Matter Chlorophyll Algae and Bacterial Numberssupporting
confidence: 89%
“…Our bacterial numbers are well in the range of other studies on the Wadden Sea (Admiraal et al 1985, Van Duyl & Kop 1988, Grossart et al 2004. Poremba et al (1999b) reported lower numbers from the North Frisian Wadden Sea. Please note that we only assessed total bacterial numbers in the water column and did not differentiate between the free-living and aggregate-associated fractions.…”
Section: Suspended Matter Chlorophyll Algae and Bacterial Numberssupporting
confidence: 89%
“…These enrichments have been previously observed in the field (Hardy and Apts, 1984). Nevertheless, in our study, autotrophic biomass and bacterial abundances were about one order of magnitude larger compared to the natural environment (Poremba et al, 1999;Sperling et al, 2012). Despite this very high biomass accumulation, we identified typical members of natural marine bacterial and eukaryotic communities with strong differences between the SML and ULW (Supplementary Figures 6, 7).…”
Section: Neuston Activity In Thick Surface Filmssupporting
confidence: 74%
“…Values for BACT, VLP, and VB were strongly correlated with the PCA 1 axis (POM/chl a; Table 2). Bacterial abundance often correlates with chl a (Cole et al 1988, Poremba et al 1999) and POM (Kimura et al 2001). In contrast to other studies, we observed no significant correlation between bacterial abundance and VLP with inorganic nutrients or DOM (Carlson & Ducklow 1996).…”
Section: Bacterial and Viral Abundancecontrasting
confidence: 56%